Hernia Umbilikalis: Ulasan Singkat - Reghina Pratiwi Hidayat; Perwisa, Inna Rahmayanti; Satria, Muhammad (Medula, 2023)
An abnormal protrusion of an organ in the fascia of the abdominal wall is called a hernia. An umbilical hernia indicates that there is a protrusion in the anterior abdominal wall. Congenital umbilical hernias occur more frequently due to failure to obliterate the umbilical blood vessels into ligaments after birth. However, congenital umbilical hernia can completely close 85-90% by the age of 5 years. Adult umbilical hernias are usually associated with increased intra-abdominal pressure, such as chronic coughing, frequent straining and large abdominal tumors, requiring surgical treatment. The clinical manifestation of an umbilical hernia is usually a protrusion in or near the navel, but if it is incarcerated or strangulated, symptoms of nausea, vomiting, difficulty defecating and abdominal pain will appear. On physical examination, you will find a lump in the navel with skin color even red to black if strangulation has occurred. In addition, to the touch it will feel warm. The most severe clinical manifestations can be symptoms of sepsis such as hypotension and tachycardia. The necessary supporting examinations include initial imaging such as ultrasound and the most sensitive, namely an abdominal CT scan. Surgical treatment for adult umbilical hernias can be done with suture or mesh repairs, while pediatric umbilical hernias can be repaired with non-absorbable sutures and umbilicoplasty for aesthetic improvement. Complications of umbilical hernia are usually related to post-surgery such as hematoma, post-operative wound infection. The prognosis for an umbilical hernia is good after surgery.